Business Development in Georgia in the Context of Globalization - Goderdzi Shanidze (ეკონომიკური პროფილი)
Business development in the modern world is actively influenced by globalization processes. This process involves deepening economic, technological and cultural integration, which directly affects the business environment of different countries. In Georgia, as a small and open economy, the impact of globalization is particularly noticeable, as international trade, investments and technologies play an important role in the country's economic growth and development.